Reliability of an exercise protocol designed to evaluate resistance exercise performance - Lambert, C. P.; Armstrong, D. E.; Jacks, D.; Armstrong, W. J.; Flynn, M. G. (The Journal of Strength and Conditioning Research, 2002)
The purpose of the present investigation was to evaluate the reliability a protocol used to assess short-term resistance exercise performance. Six men participated in this investigation after giving their consent. Subjects (N = 6) performed 6 sets of leg extensions at 80% of 10 repetition maximum (RM). Ten repetitions were performed during the first 3 sets; during the last 3 sets subjects exercised to fatigue. Ninety seconds of seated passive recovery separated each set. Subsequently, 2 experimental trials were conducted in which the exercise protocol was identical to the familiarization trial. There was a significant decline in performance from set 4 (13.5 ± 0.9 reps) to set 5 (11.9 ± 0.8 reps) and set 4 to set 6 (10.8 ± 1.0 reps), suggesting that the protocol did induce fatigue. The intraclass correlations were 0.992, 0.992, and 0.993 for the fourth, fifth, and sixth sets, respectively. The average coefficients of variation for the fourth, fifth, and sixth sets were 6.7, 2.7, and 7.1%, respectively. These data suggest that the resistance training protocol used in this investigation is reliable and may be useful in evaluating interventions designed to improve fatigue resistance.